Creative function of ecology - Hałaczek, Bernard (Studia Ecologiae et Bioethicae, 2003)
The article is an analysis of the creative function of ecology into Knowledge. This function is based on the category of valves. That's why the ecology asks “how should be”. In this way, it stands by true human problems.